PENDIDIKAN SUSILA BAGI PERUMAHTANGGA DALAM GEGURITAN SALAMPAH LAKU - Sugiharta, I Putu Suweka Oka (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2025)
Various marital problems will arise without thorough preparation. Preparation is not only related to material aspects such as the ability to meet family finances. Other preparations must also be made for the psychological aspect. Like every prospective householder, they are taught from a young age that the married life they will live in the future is full of challenges. Providing this understanding must also be done with great care to prevent individuals from being afraid of marriage. In Hinduism, marriage is a sacred obligation. Because the goal is to give birth to children with noble character. The struggle of householders to overcome various kinds of marital challenges is a noble act. Unfortunately, many prospective married people neglect to live up to the noble principles of marriage. Most people get married only because of physical love. That kind of love is not eternal. There are many cases of householders who consider their partners to be a burden after marriage. The most dominant cause is unpreparedness to solve problems that arise in marriage. When a householder loses love for his partner, household morality also collapses. The wider impact is that children raised in households with minimal immorality tend to imitate the behavior of their parents. Geguritan Salampah Laku displays the challenges of domestic life experienced directly by the author. Nevertheless, mature education means that the author is not easily provoked by emotions. The author patiently tries to improve this condition because he realizes that the goal of marriage is harmony. The moral teachings of householding in Geguritan Salampah Laku are seen in the tenacity to fight for one's household, the ability to control regrets, the ability to work together, physical and spiritual management, and the transmission of the benefits of learning. This research uses a qualitative method with a content analysis approach that is both manifest and latent.